2006
DOI: 10.1136/vr.159.9.277
|View full text |Cite
|
Sign up to set email alerts
|

Study of the effects of once daily doses of trilostane on cortisol concentrations and responsiveness to adrenocorticotrophic hormone in hyperadrenocorticoid dogs

Abstract: The effects of trilostane, a 3beta-hydroxysteroid dehydrogenase inhibitor on basal cortisol concentrations and the results of ACTH stimulation tests in dogs with pituitary-dependent hyperadrenocorticism were investigated. In eight of nine dogs trilostane suppressed the concentration of cortisol below the lower limit of the reference range (<50 nmol/l) for a mean (sd) of 3.5 (2.3) hours during the day, but for no longer than 13 hours. In another 10 dogs, there was a clear difference between the post ACTH cortis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 35 publications
2
54
0
Order By: Relevance
“…Results of this study suggest that in the population examined, serum cortisol concentrations measured before and after ACTH stimulation 9–12 hours after trilostane administration are significantly higher than those measured at 3–6 hours after trilostane administration. Although several other studies have documented that serum cortisol concentrations measured before and after ACTH stimulation are lower shortly after trilostane administration compared to several hours later, these studies examined a heterogeneous population of trilostane‐treated dogs with hyperadrenocorticism 2, 4, 7, 8. The present study is unique because it was performed in a particular subset of trilostane‐treated dogs with well‐regulated hyperadrenocorticism and low cortisol concentrations shortly after trilostane administration.…”
Section: Discussionmentioning
confidence: 99%
“…Results of this study suggest that in the population examined, serum cortisol concentrations measured before and after ACTH stimulation 9–12 hours after trilostane administration are significantly higher than those measured at 3–6 hours after trilostane administration. Although several other studies have documented that serum cortisol concentrations measured before and after ACTH stimulation are lower shortly after trilostane administration compared to several hours later, these studies examined a heterogeneous population of trilostane‐treated dogs with hyperadrenocorticism 2, 4, 7, 8. The present study is unique because it was performed in a particular subset of trilostane‐treated dogs with well‐regulated hyperadrenocorticism and low cortisol concentrations shortly after trilostane administration.…”
Section: Discussionmentioning
confidence: 99%
“…However it has been demonstrated that the effect of trilostane on basal and ACTH stimulated cortisol is considerably less than 24 hours in most cases [24]. In the same study the authors also documented six dogs with HAC whose clinical signs were poorly controlled and whose post-ACTH concentrations observed four and 24 hours after the administration of trilostane were always higher than the equivalent cortisol concentrations in four dogs whose clinical signs were controlled.…”
Section: Starting Dose and Frequencymentioning
confidence: 90%
“…However due to the relatively short lasting effects of trilostane the ACTH stimulation test varies considerably with the time of testing relative to dosing [24]. Early studies of trilostane were often conducted without the knowledge of later studies and so the clinical effects were sometimes discordant to the ACTH stimulation test results.…”
Section: Monitoringmentioning
confidence: 99%
See 1 more Smart Citation
“…Trilostane treatment, at appropriate doses and frequency of administration, may control many of the clinical and biochemical abnormalities associated with canine NOH 3, 4, 5, 6, 7. However, there is uncertainty in the literature regarding what test might serve as an objective, specific, and sensitive means of assessing therapeutic response to trilostane 6, 7, 8.…”
mentioning
confidence: 99%